Imaging method based on compressed sensing for the cognitive sparse aperture of ISAR - Feng-lian SUN; Qun ZHANG; Ying LUO; Fu-fei GU; Guo-zheng WANG (Tongxin xuebao)
Focused on the problem that different ISAR targets required different measurement dimension and different imaging time when they were imaging with compressed sensing(CS)theory,a cognitive high-resolution imaging method based on CS was proposed.According to the cognition of the sparsity of the radar target,a stochastic measurement matrix was established based on the imaging time and the target’s cross-range sparsity.An evaluate criterion of imaging quality was also present.Based on this,the cognitive high-resolution imaging was realized with the limited radar resource.Simulation results indicate that the proposed method can gain the high quality ISAR imaging with much less transmitted pulses and shorter imaging time compare to traditional imaging radar.